Guyana. Significant achievements 2010 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Guyana during 2010 are identified, with respect to the needs and interests of the country, strengthening issues such as environmental management, plant nutrition, technology, training, international trade, agrotourism, beekeeping, export, market, costs, production, good manufacturing practices and decision making. Finally, work was done on surveillance, environmental study, hydroponic systems, packaging, transportation, data management, agro-industrial sector, resilience against climate change, inclusion of women, and pest control, such as the carambola fruit fly.